Case Study: Growth Performance and Business Analysis of Brown-Marbled Grouper (Epinephelus fuscoguttatus) in Nursery and Grow-Out Cultivation - Diatin, Iis; Gandhi, Galang Raditya; Vinasyiam, Apriana (Journal of Fish Health, 2024)
Grouper fish, particularly the brown-marbled grouper (Epinephelus fuscoguttatus), are among the most economically significant marine species widely farmed and exported. This study aimed to analyze the growth performance and business analysis of the production of brown-marbled grouper, both in nursery and grow-out segments. The research was conducted using a case study method at a governmental production and research center located in Lampung Province, Indonesia. Primary data were collected through field observations, while secondary data were obtained from interviews with farm personnel. The study revealed that the nursery phase faced significant challenges, with larval survival rates as low as 4.2%. In contrast, survival rates improved considerably in larger fish, demonstrating better resilience as they grow (reaching 92-93%). From a business perspective, the grow-out activity was found to be more profitable due to lower investment costs. However, it requires a longer period to raise the fish to market size. Both nursery and grow-out operations proved to be profitable, with respective R/C ratios of 1.6-2.0. Overall, while grouper farming is economically viable, it requires careful management to overcome the high mortality in the early life stages and to optimize the investment cost-effectiveness of the nursery phase.